Control And Monitoring Of Household Electricity Use Based On Smart Energy Power Meter - Zainal Akbar; Wahidah; Nirmala Adnen (JEAT : Journal of Electrical Automation Technology, 2023)
Lack of understanding regarding electrical power usage is a common problem that often occurs. Consumers only know the amount of electricity used when they receive their monthly bill, which often causes confusion or dissatisfaction with the bill value which is considered unreasonable or too high. The aim of this research is to monitor electrical energy usage in real time and be able to display the costs of electrical energy usage. This protection system is designed using the PZEM-004t current sensor and ESP-32 microcontroller package. The reading of electrical quantities (voltage, current, active power, energy) carried out by the PZEM-004t sensor is then sent to the microcontroller, on the microcontroller the value of the electrical quantity is converted into rupiah prices and displayed on the LCD display. Monitoring via smartphone is made using a simple application creation platform, namely MIT App Inventor, connected to the internet network with a microcontroller so that electrical energy use can be monitored via smartphone. The test results show that the tool that has been created is capable of displaying the cost of electrical energy usage in accordance with the electricity tariff calculation of 900 Watts. and has a voltage measurement accuracy level of 99.4% and a current measurement accuracy level of 92.1%. If an overcurrent or short circuit occurs, the relay will disconnect the load from the PLN source. This condition will remain Off until the load returns to normal. If the load is reduced until the current is below the nominal current value of the current sensor that has been set, the relay will reconnect and the system will return to normal. In abnormal circuit conditions, before the relay breaks the circuit, the buzzer will sound.